Jewish political behavior: Liberalism or rational political tradition? The 1989 Quebec election and the Equality Party. - Gold, Irving. (University of Ottawa (Canada), 1995)
Jewish political behavior is generally characterized as liberal. This study advances an alternative conception based on rationality and pragmatism rather than reflexive liberalism. The author argues that pragmatism can dictate either liberal or non-liberal behavior for Jews, and that behavior which departs from liberalism need not be treated as a departure from an historical trend but can be regarded as a continuation of a long tradition of pragmatism. The 1989 Quebec election, which saw the election of four Equality Party of Quebec candidates, serves as the case study. The support given to the Equality candidates by the Montreal Anglophone Jewish community is examined by way of a content analysis of several pre-election editions of The Suburban, a Montreal English weekly newspaper. The Suburban is demonstrated to have been extremely supportive of the Equality Party and overwhelmingly Jewish in content and orientation. It is argued that The Suburban served as a tool for direct and indirect Jewish support for the Equality Party.
Keywords: History, Canadian.